Long-term prognosis and genetic background of cardiomyopathy in 223 pediatric mitochondrial disease patients. (15th October 2021) - Imai-Okazaki, Atsuko; Matsunaga, Ayako; Yatsuka, Yukiko; Nitta, Kazuhiro R.; Kishita, Yoshihito; Sugiura, Ayumu; Sugiyama, Yohei; Fushimi, Takuya; Shimura, Masaru; Ichimoto, Keiko; Tajika, Makiko; Ogawa-Tominaga, Minako; et al.
Abstract: Background: Cardiomyopathy is a risk factor for poor prognosis in pediatric patients with mitochondrial disease. However, other risk factors including genetic factors related to poor prognosis in mitochondrial disease has yet to be fully elucidated. Methods and results: Between January 2004 and September 2019, we enrolled 223 consecutive pediatric mitochondrial disease patients aged <18 years with a confirmed genetic diagnosis, including 114 with nuclear gene mutations, 89 patients with mitochondrial DNA (mtDNA) point mutations, 11 with mtDNA single large-scale deletions and 9 with chromosomal aberrations. Cardiomyopathy at baseline was observed in 46 patients (21%). Hazard ratios (HR) and 95% confidence intervals (CI) were calculated for all-cause mortality. Over a median follow-up of 36 months (12–77), there were 85 deaths (38%). The overall survival rate was significantly lower in patients with cardiomyopathy than in those without ( p < 0.001, log-rank test). By multivariable analysis, left ventricular (LV) hypertrophy (HR = 4.6; 95% CI: 2.8–7.3), neonatal onset (HR = 2.9; 95% CI: 1.8–4.5) and chromosomal aberrations (HR = 2.9; 95% CI: 1.3–6.5) were independent predictors of all-cause mortality. Patients with LV hypertrophy with neonatal onset and/or chromosomal aberrations had higher mortality (100% in 21 patients) than those with LV hypertrophy alone (71% in 14 patients). Conclusion: In pediatric patients with mitochondrial disease, cardiomyopathy was common (21%) and was associated with increased mortality. LV hypertrophy, neonatal onset and chromosomal aberrations were independent predictors of all-cause mortality. Prognosis is particularly unfavorable if LV hypertrophy is combined with neonatal onset and/or chromosomal aberrations. Highlights: Cardiomyopathy is related to poor prognosis in pediatric mitochondrial disease patients. However, other risk factors including genetic factors related to poor prognosis has yet to be fully elucidated. We assessed the prognosis and genetic background of cardiomyopathy in 223 pediatric mitochondrial disease patients. Cardiomyopathy was common (22%) and was associated with increased mortality. Left ventricular (LV) hypertrophy, neonatal onset and chromosomal aberrations were independent predictors of mortality. Prognosis is particularly unfavorable if LV hypertrophy is combined with neonatal onset and/or chromosomal aberrations.